Incidencia de enfermedades hemotrópicas en equinos de la Parroquia General Vernaza de la provincia del Guayas - Reyes Briones, Stalin Jimmy (2025)
Hemoparasitic diseases represent a significant problem worldwide, not only in animal health but also in public health. Among the main pathologies that affect equines are piroplasmosis and trypanosomiasis, diseases that, over time, have become a growing concern for livestock producers. These diseases can lead to severe economic losses due to decreased productivity, treatment costs, and, in some cases, death. For this reason, the present study was developed with the objective of determining the incidence of hemoparasitic diseases in equines in the General Vernaza Parish, Guayas Province. To do so, 130 equines distributed throughout the territory were sampled, including 70 horses, 56 mares, 2 fillies, and 2 colts. The data obtained were analyzed using the Percentage Method to establish the proportion of positive and negative cases for hemoparasites. The results indicated that 3.85% of the equines evaluated were positive, while 96.15% (130 cases) were negative. Among the positive cases, 3 cases of Trypanosoma (66.66%) and 2 cases of piroplasmosis (33.33%) were detected in horses. The presence of these hemoparasites highlights the importance of implementing adequate control and prevention strategies. Regarding the distribution by sex, 45% of females and 55% of males were identified, with horses being the category most susceptible to hemoparasitic diseases. These findings emphasize the need for continuous monitoring and effective disease management strategies in equine populations. Keywords: Haemoparasites, equines, economic impact, diagnosis, prevention.